2022
DOI: 10.1002/etc.5460
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 10‐ and 28‐Day Sediment Toxicity and Bioaccumulation of Fluoranthene in Hyalella azteca Using Passive Sampling Techniques

Abstract: Understanding the changes in the temporal and spatial concentrations of chemical substances in sediment toxicity tests facilitates interpretation of their toxicity and accumulation in benthic organisms because benthic organisms are affected by chemicals via multiple exposure pathways. However, such investigations using chronic sediment toxicity tests have rarely been performed. To examine the concentration profiles of a hydrophobic organic chemical using chronic spiked-sediment toxicity tests, we performed 28-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…These findings are consistent with our previous study on the semi flow-through spiked-sediment toxicity tests of BaP, fluoranthene, and chlorpyrifos with H. azteca . 6,38 Note that these results do not negate the role of sediment and DOC ingestion in the uptake of BaP by the amphipod, as C free,pore -based BCF did not exactly match that in water-only tests. As shown recently, DOC ingestion can lead to higher bioaccumulation of BaP in H. azteca .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with our previous study on the semi flow-through spiked-sediment toxicity tests of BaP, fluoranthene, and chlorpyrifos with H. azteca . 6,38 Note that these results do not negate the role of sediment and DOC ingestion in the uptake of BaP by the amphipod, as C free,pore -based BCF did not exactly match that in water-only tests. As shown recently, DOC ingestion can lead to higher bioaccumulation of BaP in H. azteca .…”
Section: Resultsmentioning
confidence: 89%
“…To measure the actual bulk C free,over more accurately, it is recommended to place the fibers away from the sediment surface, as suggested in our recent study. 38…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering their different physiologies and traits, this is not surprising; but the exact reason why VHOC concentrations in Hyalella lipid decrease to lower levels than in Lumbriculus is not clear. Recently, metabolism was suggested as an explanation for the observation that fluoranthene concentrations were lower in 28‐day‐ than in 10‐day‐exposed Hyalella (Nishimori et al, 2022). However, it should be noted that the present chemical set, for instance, also included HCB, which is not expected to be metabolized in Hyalella and Lumbriculus , but did yield the peak‐shaped uptake pattern.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, the author's mechanistic analyses concluded exposures are dependent on contaminant hydrophobicity and bioavailability, the organism's life history and habitat, and sediment characteristics. Similarly, recent work by Hiki et al, (2021Hiki et al, ( , 2023 and Nishimori et al (2022) examined the toxicokinetics of contaminant exposures to organisms in standardized sediment toxicity tests with the freshwater epibenthic amphipod Hyalella azteca. These studies are examples of the high-quality investigations needed to better understand the temporal and spatial distribution of contaminants in sediment toxicity testing systems.…”
Section: Toxicokinetic and Toxicodynamic Effects Modelingmentioning
confidence: 99%